FAKTOR PENENTU PENGAMBILAN KEPUTUSAN PEMENUHAN KEBUTUHAN NUTRISI IBU HAMIL ANEMIA GIZI - Endrawati, Susi; Suwarni, Tri (Sistem Informasi, 2016)
Objective Research to determine the factors that influence the decision-making simultaneously to fulfilling the nutritional needs of pregnant women anemia and the percentage of each factor, the views of factors: 1) knowledge / supply of nutrients; 2) the influence of culture / customs; 3) the economy; 4) support the family; and 5) decision-making.The study population was maternal anemia at four health centers working area of District Sukoharjo, using random sampling techniques and non-random sampling / non-probability sampling (samples are not random), using questionnaires and interviews. The results were analyzed with One Way Anova, multiple linear regression (multiple linear regretion), and Tukey HSD test Hoct Post / Post Hoct Bonfeeron.Result Analysis of One Way Anova in four health centers, the value of (p) 0.000 <0.05, which means there is simultaneously a significant influence, and which factors influence the Tukey HSD test Hoct Post / Post Hoct Bonfeeroni.The study concluded there was a significant influence on the decision-making factors fifth meeting nutritional needs of pregnant women anemia, namely: 1) the factors of knowledge / supply of nutrients ( health center Nguter 61.67%, 54.31% Sukoharjo, Tawangsari 51.67%, Weru 27.78%); 2) factors influence of culture / customs ( health center Tawangsari 37.5%, Nguter 34.17%, 25.86% Sukoharjo, Weru 20.37%); 3) factors economy ( health center Weru 48.15%, Tawangsari 43.33%, 39.66% Sukoharjo, Nguter 30%); 4) factor family support (health center Weru 36.29%, Nguter 34.67%, 33.79% Sukoharjo, Tawangsari 33.33%) and 5) factors decision making (health center Tawangsari 70%, Sukoharjo 50.58%, Weru 49.38% and 34.45% Nguter.